EFEKTIVITAS PENGGUNAAN BAHAN AJAR E-BOOKLET DAN INTENSITAS LATIHAN SOAL TERHADAP PENINGKATAN HASIL BELAJAR AKUNTANSI DI SMK - Br Panjaitan, Selsyana; Hendripides; Rizka, Mifta (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the effectiveness of using e-booklet teaching materials and the intensity of practice questions in improving students' accounting learning outcomes in Vocational High Schools (SMK). Students' low learning outcomes in Special Commercial Accounting Journal material are caused by the complexity of the material, limited learning resources, and the application of teacher-centered learning. This study used a quasi-experimental method with a pre-test and post-test design on two groups, namely the experimental group and the control group. Data collection techniques were carried out through learning outcome tests, observations, and questionnaires. The data were analyzed using descriptive and inferential statistical analysis. Based on the results of data analysis, the use of e-booklet teaching materials proved to be statistically effective in improving the accounting learning outcomes of vocational high school students, as shown by the results of the two-group difference test with a Sig. (2-tailed) value of 0.001 < 0.05 and reinforced by the N-Gain test results with an effectiveness level of 82.6% in the high category. Meanwhile, the intensity of practice questions was in the moderate to high category, show a statistically significant difference in learning outcomes, thus acting as a supporting factor whose effectiveness depends on the quality of practice and concept reinforcement during learning.